Investigating the in-vitro and in-vivo flavour release from 21 fresh-cut apples. (1st December 2016) - Ting, Valentina J.L.; Romano, Andrea; Soukoulis, Christos; Silcock, Patrick; Bremer, Phil J.; Cappellin, Luca; Biasioli, Franco
Highlights: 21 different apple cultivars have been investigated for flavour release profiles. PTR-ToF-MS is used to measure the in-vivo and in-vitro release of apple flavour. Selected in-vivo parameters describe the texture-flavour release relationship. Dynamics of flavour release is described by T max in relation to in-vivo release. Juiciness in apples induces more swallowing which may increase flavour perception. Abstract: In-vitro and in-vivo flavour release from 21 different apple cultivars was studied using proton transfer reaction time-of-flight mass spectrometry (PTR-ToF-MS) with a focus on the relationship between texture and volatile organic compound (VOC) emission. Generally, firm-juicy cultivars had a shorter time to first swallow ( T swal ) and a higher number of swallows ( N swal ), while softer-mealy cultivars had a longer T swal and a lower N swal. Firm-juicy cultivars containing high VOC concentrations had a short time to maximum intensity ( T max ) owing to a shorter T swal and a higher N swal as juice was released during mastication. Swallowing increased VOC flow through the nasal cavity. These results differ from previous flavour release studies with gel/gel-like model systems as juiciness/release of fluids is not a factor in such matrices. The current study, therefore, highlights the benefits of using in-vivo analysis to gain a better understanding of flavour release in real food products.